Utilization of Waste as a Raw Material to Replace Manufactured Materials For Scavengers Houses at The Kawatuna TPA Location, Palu City - Burhanuddin Burhanuddin; Luthfiah Luthfiah; Hariyadi Salenda; Nazirah Amalia (Interdiciplinary Journal and Hummanity (INJURITY), 2024)
The biggest problem in housing in Indonesia is how to deal with the housing problems of low-income communities. Houses normally inhabited by such communities are often in unhealthy environments, as are houses built only with cheap materials or waste materials. One example of the lower layers of the community is the drillers who settled in the Kawatuna TPA of Palu City. The drillers built houses using local materials such as wood, ruby or zinc roofs, and tripleks. The condition of the houses built by the rollers is very worrying, especially the lack of ventilation, which causes the air exchange to not take place properly. And a lot of garbage gathered in front of the house could lead to disease. This research will conduct a study that can find solutions to the problems faced by rollers in the Kawatuna TPA area, one of which is through the use of garbage waste as a substitute material manufactured for the construction of rolling houses. In addition to that, a redesign of the shape of the houses will be done to get a proper shape from the health side. The data analysis used is a qualitative descriptive analysis. Qualitative data obtained through data collection techniques using observation results in the Kawatuna TPA. The results of this study are simple, healthy home designs that utilize waste materials. The design of rolling houses is divided according to their activities: large type, or type A, for fixed rollers, and small type, or type B, for non-stable rollers